Creative recycling: A Note on Two Grundtvig Hymns - Balling, Jakob (Grundtvig-Studier, 2000)
Creative Recycling: A Note on Two Grundtvig Hymns By Jakob Balling This short article, which consists in a slightly revised extract from the writer’s contribution to the Grundtvig conference in York, August 24th-27th, 2000, discusses two examples of the use by Grundtvig, the hymn-writer, of central elements of old church and old European tradition. The intention is to demonstrate how, in Tag det sorte kors fra graven he resumes and transmits, in his own independent way, the idea of older Christianity - engendered in part by its Biblical view - about the convergence of times in the now of the church service, and how, in his Te Deum: O, store Gud, vi love dig he extends the perspective of the Latin source with the result that the poem becomes more old church, so to speak, than the source itself. In support of the exposition, the writer’s translation of the two hymns into English prose is attached.